Investigational approach to adenoviral conjunctivitis: comparison of three diagnostic tests using a Bayesian latent class model - Raja Sundaramurthy; Rahul Dhodapkar; Subashini Kaliaperumal; Belgode Narasimha Harish (Journal of Infection in Developing Countries)
Introduction: Highly contagious adenoviral conjunctivitis represents 15-70% of all conjunctivitis worldwide. Human adenovirus (hAdV) serotypes 3,4,7,8,19 and 37 contributes to 89% of all adenoviral conjunctivitis. Accurate and rapid diagnosis of adenoviral infections at serotype level could prevent misdiagnosis, spread of disease, unnecessary antibiotic use and increased treatment costs.